Open-Channel Flow - Chaudhry, M. Hanif; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Now in the third edition, this text on open-channel flow presents introductory material on the topic as well as up-to-date information for the planning, design, and operation of water-resource projects. It has a very strong emphasis on the application of efficient solution techniques, computational procedures, and modern methods of analysis and provides detailed coverage of steady and unsteady flows. The new edition includes a new chapter on the modeling of levee breach, new sections on hydraulic models and velocity measurements, new and updated references and problem sets and exercises, and a solutions manual. The material has been class tested over many years and the book is an ideal textbook for students in senior-level undergraduate and graduate courses on open-channel flow and hydraulic engineering, and as a reference for civil engineers needing up-to-date information on the latest developments in open-channel flow. Detailed coverage of steady and unsteady flows; Includes practical examples and sample computer programs in Python; New problem sets, some designed especially for take-home tests, and a solution manual for instructors.
Basic Concepts -- Conservation Laws -- Critical Flow -- Uniform Flow -- Gradually Varied Flow -- Computation Of Gradually Varied Flow -- Rapidly Varied Flow -- Computation of Rapidly Varied Flow -- Channel Design -- Special Topics -- Unsteady Flow -- Governing Equations For One-Dimensional Flow -- Numerical Methods -- Finite-Difference Methods -- Two-Dimensional Flow -- Sediment Transport -- Special Topics.
Keywords: Engineering geology; Fluid mechanics; Civil engineering; Pollution; Computational intelligence; Geoengineering; Engineering Fluid Dynamics; Civil Engineering; Pollution; Computational Intelligence; Channels (Hydraulic engineering); Hydrodynamics